Spatial pattern of benthic macroinvertebrate communities and their relationship with environmental variables on the East China Sea shelf. (November 2019) - Xu, Yong; Sui, Jixing; Ma, Lin; Dong, Dong; Kou, Qi; Gan, Zhibin; Gong, Lin; Yang, Mei; Li, Xinzheng; Wang, Jinbao; Wang, Hongfa
Abstract: To detect the large-scale spatial pattern of the benthic macroinvertebrate communities and the relationship with their environment on the East China Sea shelf, forty sites were sampled for benthic macroinvertebrates and environmental variables during August and September 2015. A total of 12529 benthic macroinvertebrate individuals and 274 species were collected, with crustaceans being predominant, followed by mollusks. Four communities were identified by hierarchical agglomerative cluster (HAC) analysis and cross-verified by non-metric multidimensional scaling (NMDS) ordination: an Inshore community (IC); a Transitional community (TC); a Northern offshore community (NOC); and a Southern offshore community (SOC). Significant differences in their community structure were found by permutational multivariate analysis of variance (PERMANOVA). The indicator species varied among the four communities, with Solenocera crassicornis, Sternaspis scutata and Virgularia sp. dominating IC, Solenocera koelbeli, Trachysalambria curvirostris and Nitidotellina valtonis dominating TC, Parapenaeus fissuroides, Onustus exutus and Drachiella morum dominating NOC, and Heikeopsis japonica, Solenocera pectinulata and Actiniaria dominating SOC. Significant differences among communities were detected for species number ( S ), Margalef's index ( d ), Pielou's index ( J ′), Hill's number ( N ∞ ), total taxonomic distinctness ( SΔ + ), average phylogenetic diversity ( Φ + ), total phylogenetic diversity ( SΦ + ) and abundance through statistical analyses. The redundancy analysis (RDA) model revealed that turbidity, silicate and depth were significant environmental variables influencing the benthic macroinvertebrates. Variation partitioning (VPA) showed that water characteristics had a greater impact than sediment conditions on the distribution of benthic macroinvertebrates in the East China Sea.